Defining current gaps in quality measures for cancer immunotherapy: consensus report from the Society for Immunotherapy of Cancer (SITC) 2019 Quality Summit. Issue 1 (16th January 2020) - Pai, Sara; Blaisdell, David; Brodie, Rachel; Carlson, Robert; Finnes, Heidi; Galioto, Michele; Jensen, Roxanne E; Valuck, Tom; Sepulveda, Antonia R; Kaufman, Howard L
Abstract : Background: Quality measures are important because they can help improve and standardize the delivery of cancer care among healthcare providers and across tumor types. In an environment characterized by a rapidly shifting immunotherapeutic landscape and lack of associated long-term outcome data, defining quality measures for cancer immunotherapy is a high priority yet fraught with many challenges. Methods: Thus, the Society for Immunotherapy of Cancer convened a multistakeholder expert panel to, first, identify the current gaps in measures of quality cancer care delivery as it relates to immunotherapy and to, second, advance priority concepts surrounding quality measures that could be developed and broadly adopted by the field. Results: After reviewing the existing quality measure landscape employed for immunotherapeutic-based cancer care, the expert panel identified four relevant National Quality Strategy domains (patient safety, person and family-centered care, care coordination and communication, appropriate treatment selection) with significant gaps in immunotherapy-based quality cancer care delivery. Furthermore, these domains offer opportunities for the development of quality measures as they relate to cancer immunotherapy. These four quality measure concepts are presented in this consensus statement. Conclusions: This work represents a first step toward defining and standardizing quality delivery of cancer immunotherapy in order to realize its optimal application and benefit for patients.